The Cartoon Films Using the cartoon films to improve vocabulary mastery of seventh grade junior high schools in UPTD SMPN 1 Parepare - Patahuddin; Olivia, Reni; A, Nasrullah (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2021)
Vocabulary is one of the important mastery in English. People can communicate or talk with others by creating a sentence either verbally or in writing. The function of a sentence is to convey the message or the specific intent. So that the message can be up and understandable manner of speaking. This research was based on the students problem regarding the English teaching. Especially the students vocabulary mastery. It was caused by the teaching activity applied in the classroom, where the teacher was more active than students. Consequently, the students vocabulary mastery was low. Therefore, the objective of the research is to find out whether or not the use of the cartoons films able to improve vocabulary mastery of seventh grade junior high schools in UPTD SMPN 1 Parepare. The researcher applied quasi-experimental design with two groups pretest and posttest design. The population of this research was the seventh grade students at UPTD SMPN 1 Parepare academic year 2020/2021. The sample of the research was taken by using total random sampling which consisted of 64 students from two classes taken from the population of the seventh grade students of UPTD SMPN 1 Parepare. VII.6 as the experimental class and VII.9 as the control class.The result of the data analysis shown that the students vocabulary mastery was improved. It was shown by the mean score of the pretest in the experimental class was 50.00 while the control class 55.43. Besides that, the mean score of posttest on experimental was 83.12 while on control class 64.68. It was proved the t-test 2.380 was greater than the t-table 2.000 with degree of freedom (df)=(N1+N2-2) 62 for 0.05 level of significance. It can be concluded that the results of the scores indicate that cartoon films are quite effective in implementing UPTD SMPN 1 Parepare